2016
DOI: 10.18433/j3ms5c
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Eight Green Tea Catechins on Cytochrome P450 1A2, 2C9, 2D6, and 3A4 Activities

Abstract: -PURPOSE:Green tea is a traditional beverage that has been enjoyed by the Japanese to this day. Recently, there has been an increase in the consumption of green tea beverage having high concentrations of catechins, such as (-)-epigallocatechin-3-O-gallate (EGCG). Many people tend to ingest large amounts of catechins through the frequent consumption of green tea beverage, and this dietary habit may lead to unwanted interactions between the catechins in green tea and medicinal drug. METHODS: The inhibitory effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Protein precipitation is less time consuming and requires a minimal method development (Alshammari, Al‐Hassan, Hadda, & Aljofan, ) The method also has a short incubation time of 15 min and an analysis time of 8 min compared to other methods that could take up to 60 min for incubation and 25 min for analysis (Li, Huang, Nikolic, & van Breemen, ) The calibration curves were linear over concentration ranges of 10–500 ng/mL for the metabolites under investigation. This study is the first to investigate the effects of catechin in rat hepatic CYP activity using a cocktail analysis (Chow et al, ; Satoh et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein precipitation is less time consuming and requires a minimal method development (Alshammari, Al‐Hassan, Hadda, & Aljofan, ) The method also has a short incubation time of 15 min and an analysis time of 8 min compared to other methods that could take up to 60 min for incubation and 25 min for analysis (Li, Huang, Nikolic, & van Breemen, ) The calibration curves were linear over concentration ranges of 10–500 ng/mL for the metabolites under investigation. This study is the first to investigate the effects of catechin in rat hepatic CYP activity using a cocktail analysis (Chow et al, ; Satoh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies support the cardioprotective effects of catechins through reductions in systemic blood pressure, atherosclerosis, platelet activation, and thrombus formation (Mangels & Mohler, ). One study found that CYP1A2, CYP2C9, and CYP3A4 were inhibited by catechins in green tea, and the authors recommend avoiding the consumption of large quantities of foods containing catechins when taking medications that are metabolized by these CYP enzymes (Satoh, Fujisawa, Nakamura, Takahashi, & Watanabe, ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering the health functions as shown in vivo, tea might serve as a functional food and pharmaceutical for the prevention and treatment of T2DM. Satoh et al reported that black tea aqueous extract inhibited the hydrolysis of disaccharides into monosaccharides by the α-glucosidase in the small intestine, thereby blocking the sodium-dependent glucose cotransporter 1 and glucose transporter (GLUT) 2-mediated absorption of the dietary glucose [31]. Li et al declared that TPS treatment could alleviate insulin resistance and decrease blood glucose in diabetic mice, which might be mediated by the regulation of the PI3K/Akt signal pathway as revealed by the up-regulated expression of PI3Kp85/p-Akt/GLUT4-signaling molecules [147].…”
Section: Anti-diabetic Effect In Vivomentioning
confidence: 99%
“…Catechins present in the green tea suppress the liver metabolizing enzymes like CYP 450. Inhibitory action of green tea is to CYP 450 decrease the bioavailability of sildenafil (Misaka et al, 2013;Satoh et al, 2016). Green tea also disturbs pharmacological action and absorption pattern of various drugs like MAO inhibitors, lithium and adenosine.…”
Section: Interaction With Drugsmentioning
confidence: 99%